Bloomberg visual guide to municipal bonds - Doty, Robert, 1942- (Hoboken : John Wiley & Sons, 2012)
A hands-on visual guide to understanding and investing in an important and consistently safe investment vehicleBloomberg Visual Guide to Municipal Bonds offers step-by-step guidance to the nature and diversity of municipal securities credit structures. This valuable guide demonstrates the dependability of the overwhelming majority of municipal securities, and points out particular market sectors that may yield greater rewards, but also present greater risks. This book also directs readers to good sources of up-to-date information as well as new market tools, byproducts of recent market enhancem.
Chapter 12: Investor Questions and Answers (Q & As)Appendix A: Additional Resources for You; Appendix B: Bloomberg Functionality Cheat Sheet; About the Author; Index.
Includes index.
Print version record.
Keywords: Municipal bonds -- Handbooks, manuals, etc; BUSINESS & ECONOMICS -- Investments & Securities -- Bonds; Municipal bonds; Electronic books; Handbooks and manuals